Assessing the Necessitate Quality Indicators of Hospitals\' Websites (A literature review) - SHahin Salarvand; Rohollah Sheikh Abumasoudi; Fahime Kashani; Mahnaz Samadbeik; Hamed Salarvand (Tehran University of Medical Sciences, 2016)
Background: Informative hospital website is a suitable system to exchange information between patients, hospital and health professionals and attracting consumers in hospitals. This study aimed at determining quality indicators of hospitalschr('39') websites. Materials and Methods: A literature review study was performed by searching in different databases  such as ProQuest, Ovid, Science direct, Scopus, Google scholar, PMC, PubMed  and Persian Electronic Databases  like  Iranmedex ،Magiran ، SID, Iran doc)  using Quality and Hospital website keywords. Full text of articles including English and Persian were reviewed from 2001 to 2014. Selection criteria were articleschr('39') subject which were about quality websites hospital and some articles which found from other health-related Websites (85 articles). According to the requirements and selection criteria 45 article were utilized. Results: In this review, some indicators notified such as Alexa rank, Google page rank, website type, technical content of website, information and hospital facilities, medical and admission service, online interactive services, research scientific activities, accessibility, speed of website, comprehensive plan of website, protect userschr('39') personal data, website language, user satisfaction, website map, possibility to navigating in hospital website, email of website and impartiality. Conclusion: Today, regarding to the importance of hospital websiteschr('39') quality and addressing to biotourism, it is recommended that hospital websites become so efficient, accessible, useful, credible and accessible in order to further clients satisfaction.